The Imperfect Union : Constitutional Structures of German Unification - Quint, Peter E. (Book collections on Project MUSE., 1997)
In the mid-summer of 1989 the German Democratic Republic-- known as the GDR or East Germany--was an autocratic state led by an entrenched Communist Party. A loyal member of the Warsaw Pact, it was a counterpart of the Federal Republic of Germany (West Germany), which it confronted with a mixture of hostility and grudging accommodation across the divide created by the Cold War. Over the following year and a half, dramatic changes occurred in the political system of East Germany and culminated in the GDR's "accession" to the Federal Republic itself. Yet the end of Germany's division evoked its o